Design of anti-poisoning catalysts for hydrogen oxidation reaction in next-generation anion exchange membrane fuel cells - Jiho Min; Yunjin Kim; Seunghyun Lee; Keonwoo Ko; Sourabh S. Chougule; Abhishek A. Chavan; Khikmatulla Davletbaev; Beomjun Pak; Hyelim Park; Sung-Dae Yim; Namgee Jung (Electrochemistry Communications)
Extensive research has been conducted on hydrocarbon-based ionomers and membranes with high ionic conductivity and chemical stability for next-generation anion exchange membrane fuel cells (AEMFCs). However, it is well known that the benzene groups of hydrocarbon-based ionomers seriously poison the active sites of Pt catalysts, thereby reducing hydrogen oxidation reaction (HOR) activity and AEMFC performance. Over the past years, the development of benzene-tolerant catalysts has mainly focused on metal alloy nanoparticles such as PtRu, without pursuing the design of breakthrough catalyst structures that can more effectively reduce benzene poisoning. Here, we introduce an anti-poisoning catalyst structure promoted by the synergistic effect of carbon shell encapsulation and metal alloying. The porous carbon shell encapsulating the metal nanoparticles is expected to prevent direct adsorption of benzene groups, while the alloying of Pt and Ru can reduce the benzene adsorption energy itself. Comparative electrochemical analysis results confirm that the carbon shell-encapsulated metal alloy catalyst significantly alleviate benzene poisoning, exhibiting superior HOR activity than the conventional alloys in benzyltrimethylammonium hydroxide (BTMAOH) solution.